Report on Minor Irrigation Works in Madhya Pradesh - Planning Commission (Planning Commission, 1966)
Madhya Pradesh, as its name implies, lies in the central region of India. It is bounded by the States of Uttar Pradesh on the North, Bihar on the north-east, Orissa on the south-east, Andhra Pradesh on the south, Maharashtra on the south-west. Gujarat on the west and Rajasthan on the north-west. Its superficial area is the largest of all States in India. It extends between 18.0° and 26.5° North latitudes and 74.0° and 84.5° East longitudes. There are four distinct regions, namely, Mahakoshal. Bhopal, Madhya Bharat and Vindhya Pradesh which comprise present Madhya Pradesh and which have varying codes and practices. Administratively the State is divided into seven divisions and 43 districts. The administrative map of Madhya Pradesh is shown at Fig. 1.1. Physically the Slate can be divided into five regions, namely: (1) Gird or Gwalior region: (2) Malwa Plateau: (3) Satpura range: (4) Narmada Valley: and (5) Chattisgarh Plains. The low hill ranges intersected by rivers Narmada and Sone divide the Slate into two parts. These regions are distinctly marked on Fig. 1.2.
Report on Minor Irrigation Works
Committee on Plan Projects Irrigation Team, New Delhi